Design of Hollow Cone Water Gate with Hydraulic System in Karangkates Dam - Mulyono Mulyono; M Irkham Mamungkas; Candra Dwi Febrian (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Water gate system in a dam is to control the water flow. It also controls the water surface elevation being stored or routed. The hollow cone type was designed as it has the most efficient energy of dissipation. It also has a simple construction, a relatively affordable cost, and it can be operated electromagnetically or in the hydraulic system. The hollow cone design gives a stable debit coefficient and can be implemented on a big scale. The method used in this design is the data collection and calculation of dimension scale and water gate capacity. The result of the calculation determined the capability of the hollow cone water gate to control the maximum debit of 5,9251 m³/s, the operation load of 2.875,92 kg, tensile stress around the valve 2,0108 kg/mm2. The design of the hollow cone system used the SC30C of the M20 nut.